Horizontal Head and Eye Rotations of Non-Expert Baseball Batters. - Fogt, Nick; Kuntzsch, Erik; Zimmerman, Aaron (Optometry & Visual Performance, 2019)
Purpose: The purpose of this experiment was to measure the horizontal head rotations, eye rotations, and gaze tracking responses of non-expert baseball players in tracking a pitched ball and to compare these data to those from intercollegiate baseball players. Methods: A pneumatic pitching machine propelled tennis balls toward participants at about 77mph. Participants called out numbers and the color of these numbers written on the balls. Head movements were recorded with an inertial sensor attached to a batting helmet, and eye movements were recorded with a wearable infrared video tracker. Results: Data were analyzed for 14 non-expert participants, and these data were compared to those from a group of 15 intercollegiate players. For both the non-expert and intercollegiate groups, head movements in the direction of the ball were larger than eye movements at all six elapsed times of interest. At the end of the pitch trajectory, head movements were significantly larger and gaze errors were significantly smaller for the nonexperts. There were no significant differences in the variability between the non-experts and intercollegiate participants. When the non-experts were divided by experience, the group with no baseball experience exhibited eye movements opposite to the head movement and larger head movements than the other groups. Conclusions: In tracking a pitched ball, non-expert baseball batters adopted a similar pattern of head-eye coordination to that of intercollegiate baseball batters. Non-experts with no baseball experience demonstrated larger eye movements opposite to the ball, suggesting that cancellation of the rotational vestibulo-ocular reflex may be less efficient in this group.